2000
DOI: 10.1046/j.1365-3156.2000.00604.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and survival of low birthweight infants from 0 to 9 years in a rural area of Ghana. Comparison of moderately low (1501–2000 g) and very low birthweight (1000–1500 g) infants and a local reference population

Abstract: This prospective and descriptive study was conducted to evaluate the growth and survival of 105 low birthweight (LBW, 1,000-2,000 g) infants discharged during a 4-year period from Agogo Hospital, Ghana, and followed from birth until the age of 4-9 years. Thirty-two babies were very low birthweight children (VLBW, 1,000-1,500 g) and 73 (70%) were of moderately low birthweight (MLBW, 1,501-2,000 g). At the age of 3 years, 15 children (14.2%) had not come for follow-up; of the remaining 90 children, nine (10%) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
3
1
Order By: Relevance
“…The overall LBW incidence found in this study was 6.2% for our sample of those mothers attending the Maternity Wards of the Obstetrics and Gynaecology Department of the Korle-Bu Teaching Hospital (KBTH), Accra, Ghana. This result contrasts a previous study in the community that reported a prevalence of 11% [38]. The difference could be due to early mortality rates within the Health Facility that precluded inclusion in the data capture.…”
Section: Discussioncontrasting
confidence: 97%
“…The overall LBW incidence found in this study was 6.2% for our sample of those mothers attending the Maternity Wards of the Obstetrics and Gynaecology Department of the Korle-Bu Teaching Hospital (KBTH), Accra, Ghana. This result contrasts a previous study in the community that reported a prevalence of 11% [38]. The difference could be due to early mortality rates within the Health Facility that precluded inclusion in the data capture.…”
Section: Discussioncontrasting
confidence: 97%
“…at least 2.50 kg, and three categories of low-birth-weight: 2.00–2.49, 1.50–1.99 and less than 1.50 kg. 7 , 8 , 12…”
Section: Methodsmentioning
confidence: 99%
“… 3 6 Such estimates are particularly scarce for the – mostly preterm – infants born weighing less than 1.50 kg. 7 , 8 Data from sub-Saharan Africa on the degree to which low birth weight increases the risk of mortality and illness in the post-neonatal period are lacking but are needed to target interventions. Caregivers who think an infant is likely to die may be less likely to seek care for the infant, especially if the infant is fragile and small and the affected household is poor and far from a health facility.…”
Section: Introductionmentioning
confidence: 99%
“…Van der mei et al ., in a study on comparison of NLBW and VLBW neonates’ growth with reference population (LBW neonates) showed that mean weights of MLBW and VLBW at ages of 2,6,18,48 and 96 months were lower than reference group. [8] Power et al ., in a cohort study monitored 135 very low birth weight infants (gestational age: 23-35 weeks) to 3 years of age at San Antonio, Texas, and showed that weight-gaining pattern in VLBW with gestational age ≥27 weeks was low in the first 12 months and got an ascending trend at the age of 18 months. It had an improvement until 30 months of age while growth disorder in neonates whose gestational age was ≤26 weeks was constant until the age of 3 years.…”
Section: Discussionmentioning
confidence: 99%